Pengaruh Kepercayaan, Keamanan Dan Kualitas Pelayanan Terhadap Keputusan Pembelian Pada JD.Id (Studi Kasus Pada Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Islam Malang) - Ikhwan Khulu Kudin; Budi Wahono; Fahrurrozi Rahman (UNIVERSITAS ISLAM MALANG, 2021)
AbtractAt this time the development of the times occurred very rapidly, followed by increasingly sophisticated technological developments. Several aspects of life are affected by the development of this technology. Developments are very visible in various fields, such as transportation and the most striking thing is technology, which is supported by the internet, the internet can connect internet users from all over the world so they can communicate via electronic communication. One of the Online Shop companies in Indonesia is JD.ID with the slogan Beware of being deceived, fake goods. JD.ID was formed in collaboration between JD.com and an Indonesian Partner. JD.com is one of the largest online B2C stores in China in terms of number of transactions. Jd.com is Alibaba's biggest rival, the market leader in China, JD.ID is working with Provident Capital. This research is an explanatory research with a quantitative approach. In this study, the population used was students who had registered the Faculty of Economics and Business and who made purchases at JD.ID, totaling 90 respondents. The result of this research shows that trust, safety and service quality variables simultaneously to purchasing decisions at JD.ID in FEB students of Islamic University of Malang. The variables of Trust, Safety and Service Quality partially influence the Purchasing Decision at JD.ID for FEB students of the Islamic University of Malang. Keywords: Trust, Security, Service Quality and Purchasing Decisions